Analisis Penempatan Tangga terhadap Simpangan akibat Beban Gempa dengan Metode Time History Analysis (Studi Kasus: Gedung Rawat Inap RSUD dr. Hasri Ainun Habibie) - Fitri Kiayi; Kasmat Saleh Nur; Mirzan Gani (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Indonesia has a high level of earthquake vulnerability due to its location within the Ring of Fire and at the convergence of three major tectonic plates. This condition necessitates the design of earthquake-resistant multistory buildings by considering stair elements that are integrated with the main structural system. Improper stair placement may affect structural stiffness and eccentricity and increase interstory drift, potentially leading to severe damage. This study analyzes the effect of stair position on the drift of reinforced concrete building structures using 3D modeling of three stair placement configurations from previous studies. Seismic load analysis employed the Time History Analysis method using three pairs of global earthquake records: Chi-Chi, Kobe, and El Centro. The analysis focused on evaluating interstory drift values to determine whether the stair placement configurations met safety standards. The findings indicate that stair placement significantly affects interstory drift. The Chi-Chi earthquake produced the largest interstory drift in Placement 3, particularly on the second and third floors, exceeding the allowable limit of 40 mm with values of 59.20 mm (X- direction) and 46.19 mm (Y-direction). This was followed by the El Centro earthquake, whereas the Kobe earthquake resulted in the smallest interstory drift for the same configuration, remaining below the allowable limit, with values of 27.54 mm (X-direction) and 24.15 mm (Y-direction).